Reframing jellyfish perception from “enemies” to “helpers” through Ocean Literacy - Salazar, Janire; Marambio, Macarena; Ballesteros, Ainara; Vendrell-Simón, Begoña; Gili, Josep-Maria (Frontiers in Marine Science, 2025)
Despite covering three-quarters of Earth’s surface and comprising 99% of its habitable space, the ocean remains underrepresented in formal education, contributing to widespread Ocean Literacy (OL) deficits. Jellyfish – among the earliest metazoans – inhabit all ocean basins and play vital ecological roles. Yet, they are often misrepresented and negatively perceived due to the impacts of jellyfish blooms – phenomena often linked to anthropogenic pressures – on human activities. These blooms not only have ecological consequences but also reflect a broader disconnect between society and the ocean, highlighting the need to promote awareness and foster sustainable behaviors. To help address this gap, a marine research group developed an initiative introducing OL concepts using jellyfish as a flagship species in the context of global change. In collaboration with educators, primary school teachers and students from Catalonia and Asturias (Spain), jellyfish-centered educational interventions were co-developed and tested, including teacher training, classroom implementation and open-access educational resources. Pre- and post- intervention assessments of students and teachers revealed significant improvements in marine knowledge and the development of sustainable behaviors. OL tests revealed similar misconceptions and knowledge gaps in both regions, which declined markedly after the interventions. The autonomous application of the resources by teachers without direct scientific facilitation also yielded significant learning gains. Further teacher interviews two years post-intervention showed that the initiative fostered long-term engagement. By reframing the increase in jellyfish blooms as a potential indicator of anthropogenic pressure rather than a threat, this approach contributes to cultivating ocean-aware, engaged communities committed to addressing global environmental challenges.